U Ukuran Perusahaan Memoderasi Pengaruh Profitabilitas dan Likuiditas terhadap Harga Saham - Teti Fitriansyah; Acep Komara (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to provide empirical understanding of the effect of financial performance, particularly profitability (ROA) and liquidity (CR), on stock prices, with company size as a moderating variable. This study uses a quantitative method with an associative causal approach. The research population includes transportation sector companies listed on the Indonesia Stock Exchange, and through purposive sampling, 15 companies were selected with a total of 45 observations during the 2022–2024 period. Data analysis was performed using Moderated Regression Analysis (MRA) with a Random Effect model and processed using STATA 17 software. The results showed that Return on Assets (ROA) had no significant effect on stock prices with a probability value of 0.644, while Current Ratio (CR) also showed no significant effect with a probability value of 0.351. Simultaneously, ROA and CR did not significantly affect stock prices, indicated by a Wald chi² probability value of 0.6132. However, company size significantly moderated the relationship between ROA and stock prices in a strengthening direction (p-value = 0.007), while company size weakened the effect of CR on stock prices (p-value = 0.000). These findings indicate that larger companies tend to strengthen investor confidence in profitability performance, whereas excessive liquidity in large firms may be perceived as inefficient asset management. This study shows that transportation companies need to optimize asset management efficiency and adjust liquidity strategies according to company characteristics to maintain stock value and increase investor confidence